Neonatal Mortality and Morbidity in a Tertiary Care Hospital of Coastal South India - Kannan, Raja; Rao, Suchetha; Mithra, Prasanna; Rajesh, SM; Unnikrishnan, Bhaskaran; Rekha, T (Journal of Nepal Paediatric Society, 2018)
Correction: On 13th June, Prasanna Mithra was added as an author of this paper. Introduction: Progress in new-born survival has been slow. There is a variation in neonatal death rates across states and geographical region of a country. Understanding the pattern of mortality is essential in improving new-born survival. This study was conducted to study the mortality and morbidity profile in Neonatal Intensive Care Unit (NICU) of a university teaching hospital. Material and Methods: This was a retrospective descriptive study including records of all neonates admitted in NICU from January 2015 to December 2016. Results 3623 neonates were admitted during the study period. Majority were preterm and low birth weight babies. Neonatal jaundice (41.4%) was the leading cause of admission. Major cause of morbidity was sepsis (26.2%). Average duration of stay were higher in out borns (8.4 days) compared to inborn (6.5 days) neonates. Among mortality a higher male predominance was seen. Neonatal sepsis (36.3%) was the single most common cause of mortality followed by respiratory distress syndrome (27.4%) and congenital malformations (18.6%). Out born neonates which were self-transported had higher mortality rate than transported by ambulance. Conclusion This study identifies sepsis, prematurity and low birth weight as the major causes of morbidity. Sepsis, respiratory distress syndrome and congenital malformations were the leading causes of mortality Understanding causes of neonatal mortality may help to implement interventions to promote new-born survival.